Reescolher e não desistir: reorientação profissional com estudantes de Engenharia da UFC - Rodrigues, Yangla Kelly Oliveira (2018)
The professional reorientation with Engineering students of the Technology Center (TC) of the Federal University of Ceará (FUC) has been developed two years ago by the Educational Orientation Nucleus, linked to the Assistant Directorate of Education of the center. An innovative initiative within that university. The structure of the reorientation process comprises an initial interview, six group meetings and a final, devolutionary interview. The methodology used includes the realization of group dynamics, the use of games, work with texts, dramatizations, among other techniques. Throughout this experience, of the 41 students who took part in the professional reorientation, more than half, precisely 22 students decided to stay in the same course. This result leads one to believe that the student's attendance at the right time, when he is still in university, and in which he can be guided to reflect on the reasons for his dissatisfaction with the course, if this discontent is due to aspects external to student and not to the lack of identification with the area, contributes to the reduction of evasion.